Procedure for mass-production of Neurospora tetrasperma ascospores - A. S. Sussman (Fungal Genetics Reports, 1992)
Heterokaryotic A + a cultures of N. tetrasperma produce ascospores more quickly and abundantly than A x a crosses in heterothallic species such as N. crassa. In the course of studying ascospore structure and physiology in the 1950's and 1960's, methods were developed that enabled us to obtain gram-quantities of air-dry spores. Details of the procedure never were published and it has been suggested that I do so now for the benefit of those who may want to obtain ascospores in large quantities.